Bimetallic Iridium–Carbene Complexes with Mesoionic Triazolylidene Ligands for Water Oxidation Catalysis12. Issue 4 (30th August 2013) - Petronilho, Ana; Woods, James A.; Bernhard, Stefan; Albrecht, Martin
Abstract: Two new diiridium–triazolylidene complexes were prepared as bimetallic analogues of established mononuclear water oxidation catalysts. Both complexes are efficient catalyst precursors in the presence of cerium ammonium nitrate (CAN) as sacrificial oxidant. Up to 20000:1 ratios of CAN/complex, the turnover limitation is the availability of CAN and not the catalyst stability. The water oxidation activity of the bimetallic complexes is not better than the monometallic species at 0.6 mM catalyst concentration. Under dilute conditions (0.03 mM ), the bimetallic complexes double their activity, whereas the monometallic complexes show an opposite trend and display markedly reduced rates, thereby suggesting a benefit of the close proximity of two metal centers in this low concentration regime. The high dependence of catalyst activity on reaction conditions indicates that caution is required when catalysts are compared by their turnover frequencies only. Abstract : Ditopic triazolylidene–iridium complexes were evaluated as water oxidation catalysts; the bimetallic arrangement enhances the maximum turnover frequency considerably in catalytic experiments that use low catalyst loadings.